Combining fundamental and technical analysis In stock investment (Technology) - Li, Zhannan (2018)
All the investors are trying their best to identify undervalued assets using different ways. These can be categorized into two major types. First type of investors uses technical analysis, typically the hedge fund companies and investment bank. The other type of investor focusses more on the fundamental factors, a well-known example is Warren Buffet. Long debit has done about which way is better, yet there is no scientific approve that one wins another. This project aims to bring two types of analysis methods together, using fundamental analysis to filter the foundationally strong company, and use technical analysis to indicate to investors which point is the good opportunity to buy. Beside this, different theories and hypothesis had been explored by the student. Majority of the data is gathered from the financial report of the company, SGX stock facts and bloom Bloomberg.